Prime Minister's Decree No. 909 of the year 2018 Promulgating The Executive Regulations of Law No. 2 of the year 2018 on the Comprehensive Health Insurance Scheme Serial No. 97/2018 = اللائحة التنفيذية لقانون نظام التأمين الصحي الشامل. - Egypt; The middle east library for economic services, translator. (2025)
Prime’s minster decree no. 909 of the year 2018 promulgated the Executive Regulations of Law No. 2 of the year 2018 on the Comprehensive Health Insurance Scheme – part 1: definitions and scope of application – part 2: management of the scheme – part 3: sources of finance – part 4: general provisions قرار رقم 909 لسنة 2018 بإصدار اللائحة التنفيذية لقانون نظام التأمين الصحى الشامل الصادر بالقانون رقم 2 لسنة 2018 – الباب الأول التعريفات ونطاق التطبيق – الباب الثانى إدارة النظام – الباب الثالث مصادر التمويل – الباب الرابع أحكام عامة